Cover Picture: Intramolecularly‐stabilized Group 14 Alkoxides – Promising Precursors for the Synthesis of Group 14‐Chalcogenides by Hot‐Injection Method (Z. Anorg. Allg. Chem. 11/2017). Issue 11 (1st June 2017) - Rusek, Monika; Bendt, Georg; Wölper, Christoph; Bläser, Dieter; Schulz, Stephan
Abstract : The cover picture shows the wet chemical synthesis of phase‐pure group 14/16 semiconducting materials (ME) by scrambling reactions of bistrialkylsilylchalcogenides E(SiR3 )2 with germanium, tin and lead alkoxide complexes M(OC2 H4 NR2 )2 containing a hemilabile side‐arm donor function. The reactions proceed at moderate reaction temperatures in the absence of any capping agent with elimination of the corresponding silylether. Details are discussed in the article by Monika Rusek et al. on page on page676 ff .